Numerical simulation of the influence of the pipes structure on the measurement results of a pressure differential gas concentration measuring equipment - Qian, Hanjie; Guan, Yu; Yuan, Wei; Lu, Song (IET Conference Proceedings, 2018)
Gas concentration detection device is widely used in various fields. This paper is focus on a pressure differential gas concentration measuring device [1] used in aircraft fire extinguishing system. One of the advantage of the device is the tiny structure in the device but it also leads to the hinder to measure the behavior of the flow in this region by experiment. Here, with the help of numerical simulation, we study the flow behavior in the equipment and we also do some research on the effect of pipes structure on the measurement results. The pressure field, temperature field, velocity field and the flow behavior is presented using the finite volume based solver STAR-CCM+. The effects of different diameter and arrangement of the pipes on the measurement results were compared. It is found that reducing the volume of the whole device will effectively improve the sensitivity and reduce the response time. The adjustment of the structure of the pipe can also reduce the response time. The present results help to understand the flow phenomena occurring in the device and optimizing the structure of the pipes in the equipment.